Authoritarianism as a “Wicked Problem” in Contemporary International Relations - Ficek, Ryszard (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
This study aims to explore the concept of authoritarianism, which - presented in terms of the “wicked problem” of the contemporary world – seems to be a severe challenge to presentday International Relations (IR), both in theoretical and practical dimensions. The concept of authoritarianism is defined in the article as a form of political system in which the power and material resources of the state have been centralized, appropriated, and put at the disposal of either an individual or an elitist group “in power.” In this way, the possibilities of integrating the authoritarian state – both in the political and economic dimension – with the global system of international relations are limited, and the vital administrative institutions of the state have been manipulated and appropriated. The research method applied allows for the interpretation of the discussed issues in a complex – albeit specific – systemic form, characteristic not only for politically fragile or declining countries and regions but also for those which are politically stable and economically developed. The author’s analysis allows for the presentation and reinterpretation of the issue of contemporary authoritarian regimes concerning international relations in terms that not only define but often legitimize – and repeatedly even validate – some of the most despotic, autocratic, and hegemonist forms of the political systems in modern times.

Opracowanie ma na celu przedstawienie koncepcji autorytaryzmu, który – przedstawiony w kategoriach tzw. niegodziwego problemu współczesnego świata – wydaje się poważnym wyzwaniem dla współczesnych stosunków międzynarodowych (IR), i to zarówno w wymiarze teoretycznym, jak i praktycznym. Autor artykułu definiuje pojęcie autorytaryzmu jako formę ustroju politycznego, w którym władza i zasoby materiałowo-ludzkie państwa zostały scentralizowane, zawłaszczone i oddane do dyspozycji jednostki lub elitarnej grupy „trzymającej władzę”. W ten sposób możliwości integracji państwa autorytarnego – zarówno w wymiarze politycznym, jak i gospodarczym – z globalnym systemem stosunków międzynarodowych pozostają ograniczone, a istotne instytucje administracyjne państwa zmanipulowane i zawłaszczone. Zastosowana metoda badawcza umożliwia reinterpretację omawianych zagadnień w odniesieniu do złożonej – choć specyficznej – systemowej formy, charakterystycznej nie tylko dla państw i regionów politycznie niestabilnych i upadających, ale także struktur stabilnych politycznie i rozwiniętych gospodarczo. Niniejsza analiza pozwala na ukazanie problemu współczesnych autorytarnych reżimów politycznych w kategoriach, które nie tylko definiują, ale także legitymizują – a niejednokrotnie nawet uprawomocniają – nawet jedne z najbardziej despotycznych, autokratycznych i hegemonistycznych form ustrojowych funkcjonujących we współczesnym świecie.
Keywords: authoritarianism; democracy; wicked problem; political regime; dictatorship; the rule of law; autorytaryzm; demokracja; „niegodziwy problem”; reżim polityczny; dyktatura; rządy prawa